2018
DOI: 10.1093/jnen/nly011
|View full text |Cite
|
Sign up to set email alerts
|

Early Nodal and Paranodal Disruption in Autoimmune Optic Neuritis

Abstract: Disturbances in the nodes of Ranvier are an early phenomenon in many CNS disorders, including the autoimmune demyelinating disease multiple sclerosis (MS). Using an animal model of optic neuritis, a common early symptom of MS, we have investigated nodal and paranodal compartments in the optic nerve during disease progression. Both nodes and paranodes, as identified by immunohistochemistry against sodium channels (Nav) and Caspr, respectively, were observed to increase in length during the late induction phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…During the follow‐up study of three weeks (experiment 1), even if motor deficits were mild, ONs have been pathologically involved, confirming previous works in which optic neuritis is a common feature of MOG‐EAE . Interestingly, a significant VEP delay appeared before the clinical onset of EAE (7 dpi), resembling what happens in some patients affected by MS, which could manifest visual impairments before the first motor deficits .…”
Section: Discussionsupporting
confidence: 82%
“…During the follow‐up study of three weeks (experiment 1), even if motor deficits were mild, ONs have been pathologically involved, confirming previous works in which optic neuritis is a common feature of MOG‐EAE . Interestingly, a significant VEP delay appeared before the clinical onset of EAE (7 dpi), resembling what happens in some patients affected by MS, which could manifest visual impairments before the first motor deficits .…”
Section: Discussionsupporting
confidence: 82%
“…This was shown by various analyses of the optic nerve sourced from the same mice from which the retinas were assayed for synaptic alterations. Stojic et al () found that the paranodal region of the optic nerve is an early and sensitive marker for optic neuritis. Therefore, we screened the organization of the paranodal region of the optic nerve at day 9 after immunization by immunolabeling.…”
Section: Resultsmentioning
confidence: 99%
“…At that site, it forms a cis‐complex with contactin1 (CNTN1), a GPI‐anchored cell adhesion protein of the immunoglobulin superfamily (Zeng & Sanes, ). The pathophysiological importance of CASPR1/CNTN1 in MS has been attributed to the localization of these proteins in the myelin sheath at the paranodal region of the nodes of Ranvier present along myelinated axons (Coman et al , ) including the optic nerve (Stojic et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of numbers of the nodes of Ranvier have already been described under demyelinating conditions . In studies where complete demyelination was induced, clustering of sodium channel subunit Nav1.6 was lost or greatly reduced and did not return back to control levels, even after 6 weeks of remyelination .…”
Section: Discussionmentioning
confidence: 99%